A smart nanoreactor with photo-responsive molecular switches for controlling catalytic reactions. Issue 21 (27th April 2016) - Zhao, Rong; Hu, Jie; Niu, Chengrong; Li, Yinfeng; Hu, Mengting; Liu, Rongjuan; Li, Songjun
Abstract : A smart nanoreactor with photo-responsive molecular switches was constructed through introduction of an azobenzene/α-CD supramolecular unit on mesoporous silica. Abstract : The present work was aimed at addressing the challenge in controllable reactions, namely, how to furnish the catalysts with effective and tuneable catalytic ability responding to the external stimulus. Using mesoporous silica as the supporting material with a restrained reaction place, Ag nanoparticles were encapsulated through an in situ reaction. An azobenzene/α-CD supramolecular unit was linked on the mesoporous silica to act as the photo-responsive switch, which can transform between complexation and disassociation reversibly under UV and visible light. It was found that the complexation of azobenzene with α-CD would markedly block the mass transfer process. Its disassociation, however, would not. Therefore, this smart nanoreactor indicated tuneable catalytic behaviors, which displayed high catalytic activity when exposed to UV light and weak reactivity if irradiated by visible light.